2006
DOI: 10.1124/jpet.106.108993
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Toxicity and Pharmacological Effect of Amiodarone and Amiodarone Derivatives

Abstract: The aim of this work was to compare hepatocellular toxicity and pharmacological activity of amiodarone (2-n-butyl-3-[3,5 diiodo-4-diethylaminoethoxybenzoyl]-benzofuran; B2-O-Et-Ndiethyl) and of eight amiodarone derivatives. Three amiodarone metabolites were studied, namely, mono-N-desethylamioda- A concentration-dependent increase in lactate dehydrogenase leakage from HepG2 cells and isolated rat hepatocytes was observed in the presence of amiodarone and of most analogs, confirming their hepatocellular toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 38 publications
(53 reference statements)
2
72
0
Order By: Relevance
“…The initial induction of ann-V-positive cells was not sustained at higher concentrations of DEA, which is consistent with the marked toxicity associated with 5 M DEA, a concentration that caused an even greater proportion of the cells to undergo necrosis. These DEA results are also consistent with those of other studies (Bargout et al,2000;Waldhauser et al, 2006), in which DEA increased both apoptosis and necrosis.…”
Section: Discussionsupporting
confidence: 93%
“…The initial induction of ann-V-positive cells was not sustained at higher concentrations of DEA, which is consistent with the marked toxicity associated with 5 M DEA, a concentration that caused an even greater proportion of the cells to undergo necrosis. These DEA results are also consistent with those of other studies (Bargout et al,2000;Waldhauser et al, 2006), in which DEA increased both apoptosis and necrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Midazolam was obtained as a 1 mg/ml methanolic solution from Cerilliant (Round Rock, TX (Wendt et al, 2002;Lucas et al, 2006;Waldhauser et al, 2006) or as previously described (McDonald et al, 2012). Pooled human plasma from healthy individuals, containing sodium citrate as an anticoagulant, was obtained from Innovative Research (Novi, MI).…”
Section: Methodsmentioning
confidence: 99%
“…These changes were prevented by NAC, implicating free radicals as central mediators of AMD-induced liver injury [187]. Amidarone induced a concentration-dependent increase in cell death in HepG2 cells and isolated rat hepatocytes, accompanied by a significant decrease in respiratory control ratio and oxidation of palmitate in isolated rat liver mitochondria [188]. ROS in hepatocytes were also elevated reiterating their role in induction of cell death [188].…”
Section: Amiodarone Hepatotoxicitymentioning
confidence: 99%
“…Amidarone induced a concentration-dependent increase in cell death in HepG2 cells and isolated rat hepatocytes, accompanied by a significant decrease in respiratory control ratio and oxidation of palmitate in isolated rat liver mitochondria [188]. ROS in hepatocytes were also elevated reiterating their role in induction of cell death [188]. Studies using isolated hamster liver mitochondria showed that a concentration dependent decrease in mitochondrial membrane potential on treatment with AMD, without evidence of thiobarbituric acid-reactive substances formation, suggesting that AMD brings about its effect independent of lipid peroxidation in vitro [189].…”
Section: Amiodarone Hepatotoxicitymentioning
confidence: 99%